Socratic Open-mindedness - Hare, William (Paideusis, 2009)
A philosophical conception of open-minded inquiry first emerges in western philosophy in the work of Socrates. This paper develops an interpretation of Socratic open-mindedness drawing primarily on Socratic ideas about (i) the requirements of serious argument, and (ii) the nature of human wisdom. This account is defended against a number of objections which mistakenly interpret Socrates as defending, teaching, or inducing skepticism, and neglecting the value of expert wisdom. The ongoing significance of Socratic open-mindedness as an ideal of inquiry is brought out through examination of a notorious Canadian case in the context of forensic pathology.